THE ROLE OF PUBLIC ORGANIZATIONS IN THE FORMATION OF UNITED TERRITORIAL COMMUNITIES - Глизнер, С. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article attempts to analyze the role of public organizations in the process of formation of united territorial communities. The tasks on which the public organizations worked in the framework of mini-grants were revealed. The activities of public organizations "Social Amnesty", "Podillya Agency for Regional Development" and the public center "Business Initiatives" in the territory of Ivano-Frankivsk oblast are described. The essence of the projects on which these organizations worked in the region are revealed.